Injectable temperature-sensitive hydrogel facilitating endoscopic submucosal dissection - Xu, Ruifen; Yang, Xiaoyu; Yi, Tong; Tan, Tao; Li, Zhongqi; Feng, Xuyang; Rao, Jing; Zhou, Pinghong; Hu, Hao; Zhan, Yonghua (Frontiers in Bioengineering and Biotechnology, 2024)
Endoscopic mucosal dissection requires submucosal fluid injection to provide mucosal elevation and prevent intraoperative perforation. However, the clinically applied saline mucosal elevation height is low for a short time, and multiple intraoperative injections are required, increasing the procedure's risk. In addition, recently researched submucosal injection materials suffer from cumbersome preparation, poor economy, and questionable biosafety. Here, we report a temperature-sensitive biological F-127/SA hydrogel, which has low injection pressure, long-lasting mucosal elevation ability, and good biocompatibility. The F-127/SA hydrogel exhibited controlled gelation, injectability, and structural stability as evaluated by various experiments. More importantly, the F-127/SA hydrogel exhibited a longer-lasting mucosal elevation capacity than saline in both in vitro and in vivo models. In addition, in endoscopic submucosal dissection experiments performed in experimental pigs, F-127/SA hydrogel showed a significant advantage over saline in terms of total injection volume, total procedure time, and difficulty of the surgical procedure. These results suggest that F-127/SA hydrogel is expected to be an ideal submucosal injection material.